Synthesis, Characterization and preliminary Anti-Microbial Evaluation of New Ibuprofen Hydrazide Derivatives - Zainab Dhia Kamms, Mohammed K. Hadi, (Pakistan Journal of Medical & Health Sciences, 2022)
To create a novel series of aryl propionic acid with better antimicrobial properties, new Ibuprofen (2-(4-isobutylphenyl) propionic acid) hydrazone was prepared from the reaction of Ibuprofen ethyl ester and hydrazine hydrate in the presences of different aromatic aldehyde. Anti -microbial activity was tested for all compounds against gram positive (S. pyrogen, S.aureus), gram negative (E. coli, Klebsiella pneumoniae) bacterial strains and fungal strains (candida albicans). Compound (3f) display the highest anti-bacterial activity against gram positive bacteria while compound (3e) display highest anti-bacterial activity against gram negative one, the compound (2b) showed highest anti-fungal activity compare with the other prepared compound. All the final compounds were characterized by FT-IR and 1H-NMR spectroscopy.